Ekonomi Jalan Tengah Menurut Mahasiswa Sekolah Tinggi Agama Buddha Negeri Sriwijaya - Risa Febria Ningtyas (Jurnal Ilmiah Kampus: Sati Sampajanna, 2023)
The problems studied in this study were caused by the lack of understanding of the middle way of economics according to the students of STABN Sriwijaya Tangerang Banten because as students we need to know a good economic system is applied in order to achieve prosperity and justice for the whole community. This study aims to describe the understanding of the middle way of economics according to the views of Sriwijaya stabl students. This research is a qualitative descriptive study. Sources of data in this study are active students of STABN Sriwijaya Study Program of Buddhist Business and Management semesters 3 and 5. Data collection techniques are by means of interviews and documentation.  The validity  of  the data used triangulation of sources and the data collected was analyzed using Miles and Huberman's technical analysis. The results of this study indicate that most students understand middle way economics, but it is undeniable that there are also students who do not understand middle way economics, but most students understand the principles of Buddhist middle way economics, namely economic activities carried out without hurting and harming other beings.